Circadian Rhythms Investigated on the Cellular and Molecular Levels - Gebicke-Haerter, P. J.; Pildaín, L. V.; Matthäus, F.; Schmitt, A.; Falkai, P. (Pharmacopsychiatry, 2013)
Investigations on circadian rhythms have markedly advanced our understanding of health and disease with the advent of high-throughput technologies like microarrays and epigenetic profiling. They elucidated the multi-level behaviour of interactive oscillations from molecules to neuronal networks and eventually to processes of learning and memory in an impressive manner. The small-world topology of synchronized firing through neuron-neuron and neuron-glia gap junctions is discussed as a mathematical approach to these intensively studied issues. It has become evident that, apart from some disorders caused by gene mutations, the majority of disorders originating from disturbances of rhythms arise from environmental influences and epigenetic changes. In this context, it was mandatory to think of and devise experiments on temporary scales, which exponentially increased the volumes of data obtained from time-series and rapidly became prohibitive of manual inspection. Therefore, more and more sophisticated mathematical algorithms have been developed to identify rhythmic expression of genes and to find coexpression by their clustering. It is expected that disturbed rhythmic behaviour in mental disorders is reflected in altered oscillatory behaviour of gene expression.
Keywords: circadian rhythms; sleep; mental disorders; microarrays; epigenetics; gap junctions; systems biology